Synthesis and Characterization of Medium‐/High‐Entropy M2SnC (M=Ti/V/Nb/Zr/Hf) MAX Phases. Issue 1 (6th October 2022) - Chen, Lu; Li, Youbing; Chen, Ke; Bai, Xiaojing; Li, Mian; Du, Shiyu; Chai, Zhifang; Huang, Qing
Abstract : Entropy stabilization is an effective method to design and explore MAX phases with outstanding properties via tuning constituent elements and crystal structures, which have received considerable critical attention. Currently, some medium‐/high‐entropy (ME/HE) MAX phases, whose A layers are composed of Al, S, and magnetic elements, are reported, while few discussions about ME/HE‐MAX phases with other A elements (e.g., Sn) are conducted. Herein, fully dense ME/HE‐MAX phase bulks ((TiVNb)2 SnC, (TiVNbZr)2 SnC, and (TiVNbZrHf)2 SnC) are designed and synthesized because of the chemical diversity of MAX phases. The results of Rietveld refinement of X‐ray diffraction, scanning electron microscopy, and high‐resolution scanning transmission electron microscopy‐affiliated energy‐dispersive spectrometer analysis comprehensively verify the crystal structure of ME/HE‐MAX phases. Both the electrical conductivity and the charge carrier mobility are significantly lower than the reported correlation ternary MAX phases, due to the electron scattering and structural defects in ME/HE‐MAX phase crystal structures. Similarly, the electron contribution of thermal conductivity is gradually declining; on the contrary, the phonon plays an increasingly dominant role as temperature increases. Owing to the richness in composition of MAX phases, herein, a composition design route for discovering new MAX phases and tuning their properties is indicated. Abstract : Medium/high‐entropy (ME/HE)‐MAX phases are successfully prepared with multiple principal elements at M site. Due to the increase in entropy of mixing, distortions and defects are created largely. Compared with ternary MAX phase, the contribution of electron transport to thermal conductivity of ME/HE‐MAX phases decreases with increasing temperature. Instead, phonon gradually dominates the thermal conductivity as temperature increases.